Analisis Implementasi Personal Hygiene Penjamah Makanan di Instalasi Gizi RSUD Puri Husada Tembilahan Riau - Purwanti, Tetha Enniza; Asriwati, Asriwati; Aini, Nur (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
Personal hygiene among food handlers plays a vital role in maintaining food safety in hospital settings. Initial observations in the Nutrition Unit of Puri Husada Tembilahan Hospital revealed that several hygiene practices were not fully in accordance with established standards, including incomplete use of personal protective equipment (PPE) and work behaviours that may lead to contamination. This study aimed to analyse the implementation of personal hygiene among food handlers, covering aspects such as work behaviour, health condition, personal cleanliness, work attire, training, health examinations, and existing barriers. This study employed a descriptive qualitative approach involving key, primary, and supporting informants. Data were collected through in-depth interviews, observation, and documentation, then analysed using the Miles and Huberman method and interpreted based on relevant theories and the Regulation of the Minister of Health Number 2 of 2023 on Environmental Health. The results showed that personal hygiene practices were generally implemented, particularly in handwashing and personal cleanliness. However, compliance with PPE usage was inconsistent, and routine training and health checks were not optimally conducted. Barriers included limited supervision, environmental issues, varying levels of awareness, and recruitment processes not aligned with competency standards. In conclusion, the implementation of personal hygiene has not been fully effective and requires continuous improvement.